2008
DOI: 10.1038/nchembio.129
|View full text |Cite
|
Sign up to set email alerts
|

Selective blockade of 2-arachidonoylglycerol hydrolysis produces cannabinoid behavioral effects

Abstract: 2-Arachidonoylglycerol (2-AG) and anandamide are endocannabinoids that activate cannabinoid receptors CB1 and CB2. Endocannabinoid signaling is terminated by enzymatic hydrolysis, a process that, for anandamide, is mediated by fatty acid amide hydrolase (FAAH) and, for 2-AG, is thought to involve monoacylglycerol lipase (MAGL). FAAH inhibitors produce a select subset of the behavioral effects observed with CB1 agonists, intimating a functional segregation of endocannabinoid signaling pathways in vivo. Testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

67
1,082
5
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 830 publications
(1,174 citation statements)
references
References 42 publications
67
1,082
5
5
Order By: Relevance
“…Previous studies have found that genetic deletion of FAAH leads to 10-fold increases in whole brain AEA levels 1 and that treatment with 16 or 40 mg/ kg JZL184 produces approximately 7−8-fold increases in levels of 2-AG in whole brains. 18,19,37 The present results extend these findings by revealing increases in AEA and 2-AG levels in specific brain regions. CB 1 receptor activation by exogenously applied cannabinoids, such as THC, lacks the regional selectivity and rapid metabolism of endocannabinoids.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous studies have found that genetic deletion of FAAH leads to 10-fold increases in whole brain AEA levels 1 and that treatment with 16 or 40 mg/ kg JZL184 produces approximately 7−8-fold increases in levels of 2-AG in whole brains. 18,19,37 The present results extend these findings by revealing increases in AEA and 2-AG levels in specific brain regions. CB 1 receptor activation by exogenously applied cannabinoids, such as THC, lacks the regional selectivity and rapid metabolism of endocannabinoids.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…These finding are consistent with other results showing that full MAGL inhibition produces a more extensive subset of THC-like effects than that produced by full FAAH inhibition. 18 In contrast to these findings, performance in the object recognition task and acquisition of reference memory in the Morris water maze is enhanced in MAGL −/− mice. 34 We have also found here that 20 mg/kg JZL184 does not disrupt short-term spatial memory performance in FAAH +/+ mice.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…The potency of this compound is markedly reduced (approx. 10-fold) in rat brain membranes [92], but a small number of reports detailing the antinociceptive efficacy of local administration of JZL184 in the rat have been published. Indeed, antinociceptive effects of intra-plantar administration of JZL184 have been described in both phases of the formalin model of inflammatory pain [94], and also in capsaicin-induced acute pain [95], with mechanisms involving both CB1 and CB2 receptors.…”
Section: -Ag and Pain Processingmentioning
confidence: 99%
“…MGL is a serine hydrolase with a catalytic triad represented by Ser122, His269, and Asp239. 9 Inhibitors of 2-AG degradation have been developed such as the carbamate biphenyl-3-ylcarbamic acid cyclohexyl ester (URB602), 10−12 the tetrahydrolipstatin (S)-1-((2S,3S)-3-hexyl-4-oxooxetan-2-yl)tridecan-2-yl 2-formamidoacetate (OMDM169), 13 the 4-(bis-benzo [1,3]dioxol-5-ylhydroxy-methyl)piperidine-1-carboxylic acid 4-nitro-phenyl ester 1 (JZL184), 14 the ureidic 4-(bis(4-fluorophenyl)methyl)-piperazin-1-yl)(1H-1,2,4-triazol-1-yl)methanone 2 (SAR629), 15 and their analogue (4-(bis(benzo[d] [1,3]dioxol-5-yl)methyl)-piperidin-1-yl)(1H-1,2,4-triazol-1-yl)methanone 3 (JJKK-048). 16 Despite the variety of MGL inhibitors available, the structural diversity of chemical templates explored to date remains poor.…”
Section: ■ Introductionmentioning
confidence: 99%